Land, Power and Interests: Reshaping the Law of Endowments of Agricultural Lands in Mamluk Egypt - Hussein, Dalia (AUC Knowledge Fountain, 2019)
This thesis seeks to study the development of the law of endowment of agricultural lands in Mamluk Egypt, by contextualizing historically the fatwas related to these endowments. I argue that, in light of the prevailing economic and social circumstances, legal development during this era occurred as a response to the political, social and economic interests of the religious scholars and of the ruling elite, and as a result of the interaction between the interests of the former and power of the latter.